2022
DOI: 10.3390/w14142184
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Drivers and Aquatic Ecosystem Assessment of Periphytic Algae at Inflow Rivers in Six Lakes over the Yangtze River Basin

Abstract: Periphytic algae is frequently utilized as a health indicator for ecosystems. Many research studies have been conducted in China on the periphytic algae community, but none has compared the periphytic algae community structure at inflow rivers among different lakes in the Yangtze river basin. The periphytic algae were investigated at 94 sites in inflow rivers of Dianchi Lake, Danjiangkou Reservoir, Dongtinghu Lake, Poyanghu Lake, Chaohu Lake, and Taihu Lake. Based on microscopic research, eight phyla and 126 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Thus, these regions, with their large anthropogenic N and P emissions and dense water networks, are at high risk for ecosystem damage [4,5]. The periphytic algae community structure, a health indicator for ecosystems, at inflow rivers in this area also revealed that N and P were the driving environment variables at the basin scale [11].…”
Section: Introductionmentioning
confidence: 76%
“…Thus, these regions, with their large anthropogenic N and P emissions and dense water networks, are at high risk for ecosystem damage [4,5]. The periphytic algae community structure, a health indicator for ecosystems, at inflow rivers in this area also revealed that N and P were the driving environment variables at the basin scale [11].…”
Section: Introductionmentioning
confidence: 76%
“…The phylum Cyanophyta abundance is high because this phylum can adapt to unfavorable conditions such as low CO2, low or too high temperatures, and lack of light (Hood et al 2016;Ciebiada et al 2020;Briddon et al 2022). Hu et al (2022) and Samudra et al (2022), stated that the Bacillariophyta phylum constituent of periphyton adapts to the environment, is cosmopolitan, and has a high tolerance. According to Ogi et al (2021), most Bacillariophyta adapt to aquatic environmental conditions.…”
Section: Aementioning
confidence: 99%